Women Representation in Indian Parliament - Shah, Mohd Saqib (Universal Research Reports, 2018)
The number of women who have ever served in the Indian Parliament has always been rather low. In spite of this, there has been a sluggish but steady growth in the number of women elected to parliament over the course of the last several years. Women make up roughly 14 percent of the total members in the Lok Sabha, which is the lower house of the Indian parliament. In the Rajya Sabha, which is the upper chamber, women make up approximately 22 percent of the members. This is an increase from prior years, when the percentage of women in leadership positions was significantly smaller. There have been a number of different initiatives taken, including the reserve of seats for women in local government bodies and in certain state legislatures, in an attempt to boost the number of women who participate in politics. In addition, it has been strongly recommended that political parties run a greater number of female candidates in next elections. Despite all of these efforts, however, women in India continue to encounter substantial obstacles when trying to participate in political life. Some of the most significant barriers that women encounter while attempting to join politics are rooted in cultural and societal norms. These barriers include discrimination based on gender, as well as limited access to education and resources. In order to achieve gender equality and inclusive development in India, it is vital that the views of women be heard in the process of policymaking and governance. Additionally, increasing the number of women who are represented in the parliament is critical to this goal.